2016
DOI: 10.1134/s0021364016180016
|View full text |Cite
|
Sign up to set email alerts
|

Phonon assisted resonant tunneling and its phonons control

Abstract: We observe a series of sharp resonant features in the tunnelling differential conductance of InAs quantum dots. We found that dissipative quantum tunnelling has a strong influence on the operation of nano-devices. Because of such tunnelling the current-voltage characteristics of tunnel contact created between atomic force microscope tip and a surface of InAs/GaAs quantum dots display many interesting peaks. We found that the number, position, and heights of these peaks are associated with the phonon modes invo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
(34 reference statements)
0
11
0
7
Order By: Relevance
“…The results obtained in graphene are equally applicable to a broad class of materials generally named topological insulators 4,5 . In Ref.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The results obtained in graphene are equally applicable to a broad class of materials generally named topological insulators 4,5 . In Ref.…”
Section: Introductionmentioning
confidence: 73%
“…In Ref. 4 it was shown that on the interface between the two insulating semiconductors CdTe and HgTe(Se) an inverted band structure may arise. The inverted band structure creates a metallic conducting layer associated with the Dirac gapless spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with our previous work on this system [16,19], we conclude that the three dimensional spin-orbit interaction induced by oxygen impurities is essential to the significant isotropic enhancement of B c2 . The effects of oxygen impurities could be general in oxides, thus providing us new clues to generate other exotic phenomena such as Ising superconductivity [14,35], topological nontrivial state due to band inversion [36][37][38], vortex phase transition from liquid to solid [39].…”
mentioning
confidence: 99%
“…The TCCM was extensively studied using either bosonization [8][9][10][11][12][13] or RG [14][15][16][17][18][19][20] methods. The first studies considered only some of the scattering processes produced by forward like couplings associated with the interband and the intraband interactions.…”
Section: Introductionmentioning
confidence: 99%